Withdrawal of Schizophrenia Patients - Tubalawony, Fransina; Rahmat, Rezqiqah Aulia; Mustamin, Rini; Sari, Erma Puspita; Latif, Sarifudin Andi (Asosiasi Guru dan Dosen Seluruh Indonesia, 2024)
Schizophrenia is a mental disorder in the form of changes in psychomotor, volition, emotional affect, and perception. As a result of the symptoms that appear, problems arise for clients including, lack of self-care, risk of harming themselves and others, Low Self-Esteem. The purpose of this study was to obtain an overview of the implementation, application in mental nursing care with social isolation disorders of low self-esteem with a psychological, social, spiritual approach, in accordance with knowledge and skills. The research method uses a literature study method and case study with a comprehensive nursing process approach. The results of the study in Nursing Care have been given to clients and documented. The conclusion of this study is that several obstacles were encountered when the author conducted the assessment where the family as the client's support system was not present during the assessment so that some data were difficult to clarify.